2018
DOI: 10.18805/lr-3854
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous selection model based evaluation of arsenic tolerance in black gram (Vigna mungo L.) using morphological parameters

Abstract: The evaluation of black gram under arsenic stress is important to identify the arsenic-tolerant genotypes for cultivation in arsenic affected soil and for crop improvement programs. Thirty-two black gram genotypes were received from Indian Institute of Pulses Research (IIPR) Kanpur, India was grown in sand and exposed to three arsenic toxicity levels (control, 150 and 300 µM NaAsO 2 ). Root length, root weight, shoot length, shoot weight and total biomass of plants were recorded in the vegetative stage.The pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…A clear damage on membrane, reduction in chlorophyll and relative leaf water content were observed in arsenic treated plans (Jahid A Malik et al 2011). Shamim and Pandey, (2019) also reported that morphological characters of almost all thrty two black gram genotypes were significantly decreased with increased concentration of arsenic in supplied nutrients, shoot length; root length was less affected, whereas shoot weight, root weight and total biomass were significantly decreased under arsenic stress condition.…”
Section: Arsenic In Plants and Legumesmentioning
confidence: 93%
“…A clear damage on membrane, reduction in chlorophyll and relative leaf water content were observed in arsenic treated plans (Jahid A Malik et al 2011). Shamim and Pandey, (2019) also reported that morphological characters of almost all thrty two black gram genotypes were significantly decreased with increased concentration of arsenic in supplied nutrients, shoot length; root length was less affected, whereas shoot weight, root weight and total biomass were significantly decreased under arsenic stress condition.…”
Section: Arsenic In Plants and Legumesmentioning
confidence: 93%